Thermoplastic Electrodes for Detection of Escherichia coli - Ozer, Tugba; McCord, Cynthia; Geiss, Brian J.; Dandy, David; Henry, Charles S. (ELECTROCHEMICAL SOC INC, 2021)
A new amine functionalized electrochemical immunosensor for label-free detection of Escherichia coli using modified thermoplastic electrodes is reported for the first time. The E. coli-specific antibody was immobilized on diazonium-modified TPEs. The modification process was monitored using cyclic voltammetry and electrochemical impedance spectroscopy using the hexacyanoferrate redox couple as the electrochemical probe. The linear range was from 1 x 10(3) to 1 x 10(5) CFU ml(-1) with a linear correlation of 0.9823 and limit of detection of 27 CFU ml(-1) for E. coli (DH5 alpha strain) in phosphate buffered saline solution as a model system. The specificity of the proposed immunosensor was demonstrated by showing selective detection in the presence of different bacteria. The biosensor was successfully applied to urine samples spiked with 0.5 x 10(5) CFU ml(-1) and 1 x 10(5) CFU ml(-1) E. coli and obtained good recoveries 99% and 110%, respectively. The proposed system should be well suited for selective and sensitive detection of different pathogenic bacteria.
Keywords: LABEL-FREE DETECTION; E.-COLI; RAPID DETECTION; ELECTROCHEMICAL IMMUNOSENSOR; IMPEDIMETRIC IMMUNOSENSOR; PATHOGEN DETECTION; CARBON ELECTRODE; BIOSENSOR; IDENTIFICATION; BACTERIA; Electrochemistry; Materials Science